Neurocognitive bases of emotion regulation development in adolescence - Ahmed, Saz P. (Dev Cogn Neurosci, 2015)
Emotion regulation is the ability to recruit processes to influence emotion generation. In recent years there has been mounting interest in how emotions are regulated at behavioural and neural levels, as well as in the relevance of emotional dysregulation to psychopathology. During adolescence, brain regions involved in affect generation and regulation, including the limbic system and prefrontal cortex, undergo protracted structural and functional development. Adolescence is also a time of increasing vulnerability to internalising and externalising psychopathologies associated with poor emotion regulation, including depression, anxiety and antisocial behaviour. It is therefore of particular interest to understand how emotion regulation develops over this time, and how this relates to ongoing brain development. However, to date relatively little research has addressed these questions directly. This review will discuss existing research in these areas in both typical adolescence and in adolescent psychopathology, and will highlight opportunities for future research. In particular, it is important to consider the social context in which adolescent emotion regulation develops. It is possible that while adolescence may be a time of vulnerability to emotional dysregulation, scaffolding the development of emotion regulation during this time may be a fruitful preventative target for psychopathology.